Loving lord ash eaudiobook - MacKenzie, Sally (Duchess of Love, 2015)
Kit, the Marquis of Ashton, is in a sticky wicket. He married young and for love—how naïve. He discovered his mistake the very day of his wedding, but he is saddled now with a wife he's reluctant to trust. And however much evidence he gathers against faithless Jess, he can't seem to prove her guilt to the final judge—his foolish heart. Jess knows she's bobbled her marriage, however innocently. A fairytale wedding makes no difference if she hasn't got the marquis charmed to show for it. Well, she's had enough of accidental encounters with naked gentlemen and near misses explaining things to her husband. It's time to buck up and go win her man back—even if she has to fight very dirty indeed. Contains mature themes.